New Insights in to the Intrinsic and Acquired Drug Resistance Mechanisms in Mycobacteria - Nasiri, Mohammad J.; Haeili, Mehri; Ghazi, Mona; Goudarzi, Hossein; Pormohammad, Ali; Imani Fooladi, Abbas A.; Feizabadi, Mohammad M. (Frontiers in Microbiology, 2017)
Infectious diseases caused by clinically important Mycobacteria continue to be an important public health problem worldwide primarily due to emergence of drug resistance crisis. In recent years, the control of tuberculosis (TB), the disease caused by Mycobacterium tuberculosis (MTB), is hampered by the emergence of multidrug resistance (MDR), defined as resistance to at least isoniazid (INH) and rifampicin (RIF), two key drugs in the treatment of the disease. Despite the availability of curative anti-TB therapy, inappropriate and inadequate treatment has allowed MTB to acquire resistance to the most important anti-TB drugs. Likewise, for most mycobacteria other than MTB, the outcome of drug treatment is poor and is likely related to the high levels of antibiotic resistance. Thus, a better knowledge of the underlying mechanisms of drug resistance in mycobacteria could aid not only to select the best therapeutic options but also to develop novel drugs that can overwhelm the existing resist¬ance mechanisms. In this article, we review the distinctive mechanisms of antibiotic resistance in mycobacteria.